Educational STEM Project Based on Programming - Elena Segade; Jose Balsa; Carmen Balsa (Proceedings, 2019)
We propose a sequence of activities to be programmed to improve the learning of Science, Technology, Engineering and Mathematics in Secondary Education. This proposal consists on generate and transform images and figures programming in Octave. This enables the students to use basic and iterative instructions to construct a complex program, understand and structure problems, logic reformulation of problems, design of systematic processes for the resolution, generalization and comparison of solutions. Initial analyses of the implementation of the activities will be presented.